DNA-binding studies of mixed ligand cobalt(III) complexes - Barve, A. C.; Ghosh, Smita; Kumbhar, A. A.; Kumbhar, A. S.; Puranik, Vedavati G. (Transition Metal Chemistry, 2005)
The DNA binding characteristics of mixed ligand complexes of the type [Co(en)(2)(L)]Br-3 where en = N,N'-ethylenediamine and L = 1,10-phenanthroline (phen), 2,2'-bipyridine (bpy), 1,10-phenanthroline-5,6-dione (phendione), dipyrido[3,2-a:2',3'-c]phenazine (dppz) have been investigated by absorption titration, competitive binding fluorescence spectroscopy and viscosity measurements. The order of intercalative ability of the coordinated ligands is dppz > phen > phendione > bpy in this series of complexes.

Diethyl [(5-chloro-2-hydroxyanilino)(4-chlorophenyl)methyl]phosphonate - Krishnaiah, M.; Babu, V. H. H. Surendra; Prasad, G. Syam; Reddy, C. Suresh; Puranik, Vedavati G. (Acta Crystallographica Section E-Structure Reports Online, 2009)
In the title compound, C17H20Cl2NO4P, the P atom is bonded in a distorted tetrahedral environment. The dihedral angle between the two benzene rings is 80.5 (1)degrees. In the crystal structure, intermolecular O-H center dot center dot center dot O and N-H center dot center dot center dot O hydrogen bonds link pairs of molecules into centrosymmetric dimers. These dimers, are in turn, linked by weak intermolecular C-H center dot center dot center dot O hydrogen bonds into one-dimensional chains along [010]. Additional stabilization is provided by very weak C-H center dot center dot center dot Cl interactions.

Diastereoselective synthesis of 1,1,4-trisubstituted-2,3,4,9-tetrahydrospiro-beta-carbolines via glacial acetic acid catalyzed pictet - spengler reaction - Shumaila, Abdullah M. A.; Puranik, Vedavati G.; Kusurkar, Radhika S. (Arkivoc, 2011)
The Pictet-Spengler reaction of substituted tryptamines with cyclic ketones using glacial acetic acid afforded only one diastereomer of unreported 1,1,4-trisubstituted-2,3,4,9-tetrahydrospiro-beta-carbolines. The stereoselectivity in the reaction has been demonstrated using unsymmetrical ketones and single-crystal X-ray analysis of one of the spiro products in the form of base, its sulfate and hydrochloride salts, which indicated the formation of only the R, R diastereomer.
Keywords: 1; 3; 4; 4-Trisubstituted-2; 9-tetrahydrospiro-beta-carbolines; beta-substituted tryptamine; Diastereoselective Pictet-Spengler reaction; Glacial acetic acid

Diastereoselective synthesis of tetrasubstituted-octahydro-3,6-diazacarbazoles and tetrasubstituted-3,6-diazacarbazoles via double Pictet-Spengler reaction - Shumaila, Abdullah M. A.; Puranik, Vedavati G.; Kusurkar, Radhika S. (Tetrahedron Letters, 2011)
Pictet-Spengler condensation of 2,5-bis(2-phenyl-1-aminoethyl)pyrrole using glacial acetic acid afforded only one diastereomer of unreported tetrasubstituted-octahydro-3,6-diazacarbazoles. These were readily dehydrogenated to tetrasubstituted-3,6-diazacarbazoles. The stereoselectivity in the Pictet-Spengler reaction has been demonstrated using single crystal X-ray analysis. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: 2; 5-Bis(2-phenyl-1-aminoethyl)pyrrole; 6-diazacarbazoles; Diasteroselective Pictet-Spengler reaction; Glacial acetic acid; Tetrasubstituted-3; Tetrasubstituted-octahydro-3

Dibutyl phthalate, a secondary metabolite from mimusops elengi - Ruikar, A. D.; Gadkari, T. V.; Phalgune, U. D.; Puranik, Vedavati G.; Deshpande, N. R. (Chemistry of Natural Compounds, 2011)

Design, synthesis, structural characterization by IR, 1H, 13C, 15N, 2D-NMR, X-ray diffraction and evaluation of a new class of phenylaminoacetic acid benzylidene hydrazines as pfENR inhibitors - Samal, Ramanuj P.; Khedkar, Vijay M.; Pissurlenkar, Raghuvir R. S.; Bwalya, Angela Gono; Tasdemir, Deniz; Joshi, Ramesh A.; Rajamohanan, P. R.; Puranik, Vedavati G.; Coutinho, Evans C. (Chemical Biology & Drug Design, 2013)
Recent studies have revealed that plasmodial enoyl-ACP reductase (pfENR, FabI), one of the crucial enzymes in the plasmodial type II fatty acid synthesis II (FAS II) pathway, is a promising target for liver stage malaria infections. Hence, pfENR inhibitors have the potential to be used as causal malarial prophylactic agents. In this study, we report the design, synthesis, structural characterization and evaluation of a new class of pfENR inhibitors. The search for inhibitors began with a virtual screen of the iResearch database by molecular docking. Hits obtained from the virtual screen were ranked according to their Glide score. One hit was selected as a lead and modified to improve its binding to pfENR; from this, a series of phenylamino acetic acid benzylidene hydrazides were designed and synthesized. These molecules were thoroughly characterized by IR, 1H, 13C, 15N, 2D-NMR (COSY, NOESY, 1H-13C, 1H-15N HSQC and HMBC), and X-ray diffraction. NMR studies revealed the existence of conformational/configurational isomers around the amide and imine functionalities. The major species in DMSO solution is the E, E form, which is in dynamic equilibrium with the Z, E isomer. In the solid state, the molecule has a completely extended conformation and forms helical structures that are stabilized by strong hydrogen bond interactions, forming a helical structure stabilized by N-H...O interactions, a feature unique to this class of compounds. Furthermore, detailed investigation of the NMR spectra indicated the presence of a minor impurity in most compounds. The structure of this impurity was deduced as an imidazoline-4-one derivative based on 1H-13C and 1H-15H HMBC spectra and was confirmed from the NOESY spectra. The molecules were screened for in vitro activity against recombinant pfENR enzyme by a spectrophotometric assay. Four molecules, viz. 17, 7, 10, and 12 were found to be active at 7, 8, 10, and 12m concentration, respectively, showing promising pfENR inhibitory potential. A classification model was derived based on a binary QSAR approach termed recursive partitioning (RP) to highlight structural characteristics that could be tuned to improve activity.
Keywords: ADMET; docking; enoyl-ACP reductase; FabI; hydrogen bonding; NMR; phenylaminoacetic acid benzylidene hydrazine; Plasmodium falciparum; Plasmodium falciparum enoyl-ACP reductase; QSAR; recursive partitioning; X-ray diffraction

Design, synthesis and cytotoxicity of novel N-benzylpiperidin-4-one oximes on human cervical cancer cells - Dindulkar, Someshwar D.; Bhatnagar, Ira; Gawade, Rupesh L.; Puranik, Vedavati G.; Kim, Se-Kwon; Anh, Dong Hyun; Parthiban, Paramasivam; Jeong, Yeon Tae (Journal of Chemical Sciences, 2014)
A series of fifteen diversified N-benzylpiperidin-4-one oximes were synthesized and characterized by their NMR spectral data. Additionally, single-crystal XRD analysis was performed for the representative symmetrically and unsymmetrically substituted molecules. All the synthesized oximes from unsymmetrical ketones existed as E-isomer as witnessed by their NMR and XRD data. Among the synthesized target compounds that evaluated for their in vitro cytotoxicity against human cervical carcinoma (HeLa) cells, five compounds were potent with IC50 < 17 mu M. 1-Benzyl-2,6-bis(4-isopropylphenyl)-3-methylpiperidin-4-one oxime 3c with an IC50 of 13.88 mu M was found to be the best active compound as depicted by the microscopic analysis.
Keywords: Cytotoxicity; HeLa cells; N-benzylpiperidin-4-one oximes; single-crystal XRD

Divergent total synthesis of 1,6,8a-tri-epi-castanospermine and 1-deoxy-6,8a-di-epi-castanospermine from substituted azetidin-2-one (beta-lactam), involving a cascade sequence of reactions as a key step - Tiwari, Dipak Kumar; Bharadwaj, Kishor Chandra; Puranik, Vedavati G.; Tiwari, Dharmendra Kumar (Organic & Biomolecular Chemistry, 2014)
A divergent, short, and novel total synthesis of 1,6,8a-tri-epi-castanospermine (7) and 1-deoxy-6,8a-di-epi-castanospermine (8) has been developed via a common precursor, 15, obtained from D-mannitol derived beta-lactam. The key step involves a one pot cascade sequence of trimethyl sulfoxonium ylide based cyclization of epoxy sulfonamide 14 via epoxide ring opening, one carbon homologation followed by intramolecular cyclization.